Research on the control strategy of energy storage participation in power system frequency regulation. (22nd October 2020) - Li, Junhui; Gao, Zhuo; Mu, Gang; Fan, Xingkai; Zhang, Zheshen; Zou, Jiajun
Summary: Large‐scale wind power integrated the power system may result in a challenge for frequency regulation because of the variable nature of wind. Energy storage system (ESS) is an effective measure against the challenge of frequency regulation caused by wind power. Aiming to solve the problem that the response time of traditional turbines can hardly meet frequency regulation demand, this article proposes a strategy for ESS which can adaptively adjust the output coefficient of ESS according its state of charge (SOC). And the relationship between the frequency regulation effect and the size of ESS is established. Firstly, the reference power of ESS is obtained based on fuzzy theory. Secondly, the principle of giving priority to ESS is adopted, and the actual output is determined according to the SOC. Finally, the output of the thermal power unit is determined based on the penalty power of ESS. The case analyzed shows that the proposed strategy has a significant effect on the improvement of the frequency deviation and the CPS1, and the maintenance of SOC. Moreover, it is shown that the 100 MW/50 MWh ESS can increase the CPS1 index by 57.1% in response to the AGC frequency regulation. Abstract : This article proposes an AGC frequency regulation control strategy based on SOC partition. The simulation results show that the proposed strategy has a significant effect on the improvement of the frequency deviation and the maintenance of SOC. Moreover, it is shown that the 100 MW/50 MWh ESS can increase the CPS1 index by 57.1%.